2011
DOI: 10.1242/dev.056069
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration inDrosophilaoptic lobe neurons is controlled byeyeless/Pax6

Abstract: SUMMARYIn the developing Drosophila optic lobe, eyeless, apterous and distal-less, three genes that encode transcription factors with important functions during development, are expressed in broad subsets of medulla neurons. Medulla cortex cells follow two patterns of cell movements to acquire their final position: first, neurons are arranged in columns below each neuroblast. Then, during pupation, they migrate laterally, intermingling with each other to reach their retinotopic position in the adult optic lobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…Therefore, NBs of different ages can be observed together in one snapshot (Egger, Boone, Stevens, Brand, & Doe, 2007; Yasugi, Umetsu, Murakami, Sato, & Tabata, 2008). These NBs generate GMCs, which then produce medulla neurons that form chains below each NB, with the first-born neurons located in the deepest position and latest-born neurons in the most superficial position, near the NB (Hasegawa et al, 2011; Morante, Erclik, & Desplan, 2011). Recently, the developing medulla has emerged as a new powerful system for studying temporal patterning of NBs (Li et al, 2013; Suzuki, Kaido, Takayama, & Sato, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NBs of different ages can be observed together in one snapshot (Egger, Boone, Stevens, Brand, & Doe, 2007; Yasugi, Umetsu, Murakami, Sato, & Tabata, 2008). These NBs generate GMCs, which then produce medulla neurons that form chains below each NB, with the first-born neurons located in the deepest position and latest-born neurons in the most superficial position, near the NB (Hasegawa et al, 2011; Morante, Erclik, & Desplan, 2011). Recently, the developing medulla has emerged as a new powerful system for studying temporal patterning of NBs (Li et al, 2013; Suzuki, Kaido, Takayama, & Sato, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work on the migration has shown that GMC-1àRP2/sib undergo a complex 3-step migration and Wingless (Wg) signaling is necessary for the step 2 and step 3 migrations (Bhat, 2007). Recent work has shown that there is an active migration process going on in the optic lobe (Morante et al, 2011; Hasegawa et al, 2011). For example, medulla cortex cells in the optic lobe oerform two patterns of cell migrations to acquire their final position.…”
Section: Introductionmentioning
confidence: 99%
“…melanogaster , the compound eyes and most head structures (head capsule, antenna, ocelli) develop entirely from the eye-antennal discs [75], in which process ey gene is involved in cell proliferation, differentiation and migration/adhesion [76, 77]. The headless phenotype characterized by the lack of structures derived from eye-antennal discs suggests massive cell death during development [56, 78].…”
Section: Discussionmentioning
confidence: 99%
“…As evident from acridine orange staining of RpPax6 expressed larva and rescue of headless by the expression of the baculovirus P35 protein in eye-antennal discs (Fig 8D), the headless phenotype of UAS-RpPax6/ey-GAL4 pharates results from the induction of apoptosis by expression of RpPax6 . Paradoxically, authentic Pax genes are associated with differentiation, proliferation and anti-apoptosis during development process [76, 77]. Inhibition of ey [58, 79] as well as other Pax genes including Pax2 , Pax8 [80], Pax3 and Pax7 [81] induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%